Enhancement of learning through field study - Tesila Kandamby (OmniaScience, 2018)
Learning is more concerned in engineering education as students need to do deep learning to understand the engineering principles for practice. Engineering is a practicing profession. Therefore, providing learning environment is required for the subjects of engineering disciplines to enable students to learn in depth. By knowing this phenomenon, field study was conducted as a group study for the civil engineering subject of building construction allowing students to learn and gain knowledge by observing construction activities in construction projects in addition to the lectures in usual classroom. At the end of the study, it is found that field study is useful for learning and students acquire knowledge and understand the application of theory at real situation. In addition, students develop skills for working as a team by organizing their works, sharing knowledge, discussing with relevant technical personnel at work site and achieving the targets within the given time frame.  It is realized that teacher's role is vital to make the study successful in the ways of organizing field study, conducting discussion classes to assist students, monitoring the progress and giving the feedback of the students' performance during the course of field study producing excellent results while satisfying the objectives of both teacher and students.